Archimedes to Hawking : laws of science and the great minds behind them - Pickover, Clifford A. (New York : Oxford University Press, 2008)
Describes the lives and works of scientific lawgivers in chronological order, from Newton to Faraday, Ohm, and Hawking, covering over forty eponymous laws, their relation to theory, and the geographical distribution of great scientific minds.
Includes bibliographical references (p. [501]-503) and index.
Booklist.
Adult
Keywords: Physical laws -- History; Science -- Methodology -- History; Science -- Philosophy -- History; Scientists -- Biography; Science -- Methodology -- History; Science -- Philosophy -- History; Scientists -- Biography